The heart matters when the liver shatters! Cirrhotic cardiomyopathy: frequency, comparison, and correlation with severity of disease - Naqvi, Iftikhar Haider; Mahmood, Khalid; Naeem, Muhammad; Vashwani, Aneel Sham; Ziaullah, Syed (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction : Cirrhotic cardiomyopathy is a visor complication among patients with cirrhosis of the liver, manifesting during stress, exertion, transjuglar intrahepatic portosystemic shunt (TIPS), or liver transplantation. Cirrhotic cardiomyopathy is reported to be most common cause of post transplant mortality after rejection of 7% to 21%. Aim: To determine the frequency of cirrhotic cardiomyopathy and was further designed to compare parameters of cardiac dysfunction in patients with or without cirrhotic cardiomyopathy. Material and methods : All confirmed cases of cirrhosis with various aetiologies were enrolled. Resting ejection fraction (EF) was determined in all patients. Patients were grouped with resting EF 55% (without cardiomyopathy). Stress echocardiography with dobutamine infusion in both groups yielded an increase of less than 10% in left ventricular (LV) EF at peak dobutamine infusion confirming systolic dysfunction. The diastolic dysfunction (E/A ratio), electrocardiographic parameter (prolong QT interval), and cardiac biomarker (pro NT BNP) were also determined in both the groups to confirm cirrhotic cardiomyopathy. Results : Among 89 patients with cirrhosis, 35 (39.32%) had cirrhotic cardiomyopathy. All components of cirrhotic cardiomyopathy, like systolic dysfunction, diastolic dysfunction, prolong QT interval, and cardiac biomarkers, were found to be statistically significant (p = 0.001) when compared with patients without cardiomyopathy. Cirrhotic cardiomyopathy parameters were positively correlated with advancing liver disease. Conclusions : Cirrhotic cardiomyopathy is a frequent but unmasked complication in cirrhosis of the liver. All components of cardiac dysfunction, such as systolic, diastolic, and electrocardiographic changes, are present in patients with cirrhotic cardiomyopathy. Cirrhotic cardiomyopathy is positively correlated to severity of liver disease.